Essential Biological Psychology. - Martin, G. Neil (Essential psychology series., 2003)
Covering all the major topics within biopsychology, and evaluating the most up-to-date findings, this textbook is essential reading for first and second year psychology undergraduates as well as anyone studying courses in neuropsychology or behavioural neuroscience.